Shirley, I jest! : a storied life - Williams, Cindy; Smitherman, Dave (Guilford, Connecticut : Globe Pequot Press, 2017)
Cindy Williams, half of the comedic duo of Laverne & Shirley, has had a wild and lively career in show business. This book is an engaging and heartfelt journey from Williams's blue collar roots to unexpected stardom-from being pranked by Jim Morrison while waiting tables at Whisky a Go Go to starring in one of the most iconic shows on television. With wit and candor, Cindy tells stories of her struggles as a child growing up with meager means and dreaming of becoming an actress. She also shares many misadventures and amusing anecdotes about some of the most famous actors in Hollywood. Never taking herself too seriously, Cindy finds humor and irony in the challenging world of show business
Foreword / by Ed Begley, Jr -- Valley Texas gal -- Love, peace and happiness -- Back to the valley -- High hopes -- Some enchanted evening -- Raw talent -- The big show -- The mirthful mouse -- The adventures of Laverne and Shirley -- Outtakes -- Epilogue.
Keywords: AUTOBIOGRAPHIES